2011
DOI: 10.1002/fld.2632
|View full text |Cite
|
Sign up to set email alerts
|

Numerical prediction of turbulent flow structure generated by a synthetic cross‐jet into a turbulent boundary layer

Abstract: SUMMARY A detailed numerical study using large‐eddy simulation (LES) and unsteady Reynolds‐averaged Navier–Stokes (URANS) was undertaken to investigate physical processes that are engendered in the injection of a circular synthetic (zero‐net mass flux) jet in a zero pressure gradient turbulent boundary layer. A complementary study was carried out and was verified by comparisons with the available experimental data that were obtained at corresponding conditions with the aim of achieving an improved understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…They built a more complete physical mode for flow separation delay which involves a hierarchy of vortical structures showed in Figure 2.22b. Note that both the primary hairpin voritces and the pair of streamwise vortices near to the wall are similar to what are observed in studies of SJs in an attached TBL as discussed in previous section 2.3.2 (Dandois& Garner, 2006;Wu & Leschziner, 2009;Javadi & El-Askary, 2011) Zhang & Zhong (2011). suggested that the induced streamwise vortex pair, which are found locate closer to the wall and persist during a substantial portion of the actuation cycle, provides the main mechanism of flow separation delay by producing a downwash motion, which bring relatively more energetic fluids towards the wall.…”
supporting
confidence: 76%
See 4 more Smart Citations
“…They built a more complete physical mode for flow separation delay which involves a hierarchy of vortical structures showed in Figure 2.22b. Note that both the primary hairpin voritces and the pair of streamwise vortices near to the wall are similar to what are observed in studies of SJs in an attached TBL as discussed in previous section 2.3.2 (Dandois& Garner, 2006;Wu & Leschziner, 2009;Javadi & El-Askary, 2011) Zhang & Zhong (2011). suggested that the induced streamwise vortex pair, which are found locate closer to the wall and persist during a substantial portion of the actuation cycle, provides the main mechanism of flow separation delay by producing a downwash motion, which bring relatively more energetic fluids towards the wall.…”
supporting
confidence: 76%
“…For the hairpin vortices case, they revealed a hierarchy of coherent vortices consisting of primary hairpin vortices, secondary vortices and horseshoe vortex using Q-criterion (Hunt et al, 1988) in Figure 2.14a. For the tilted vortex ring case, the vortex ring was found accompanied by a pair of trailing vortices which further induced a pair of tertiary structures as shown in .16: (a)Vortices generated by single circular SJs in TBL, and (b) contours of phase-averaged streamwise velocity in a wall-parallel plane (Javadi & El-Askary, 2011).…”
Section: Single Sjs In Attached Crossflowsmentioning
confidence: 97%
See 3 more Smart Citations